Tax Avoidance in Family Business: The Ethical Perspective of CEO Gender - Candra Kirana, Linlin (Atestasi : Jurnal Ilmiah Akuntansi, 2026)
Purpose: This study aims to map the global research landscape on tax avoidance in family businesses through a bibliometric analysis, focusing on the ethical implications of CEO gender. Research Design and Methodology: A bibliometric analysis was conducted on 550 Scopus-indexed documents (2017-2025) using RStudio and Bibliometrix to assess performance and conduct science mapping. Findings and Discussion: The analysis identifies corporate governance as a central theme and reveals a strong association between female CEOs/gender-diverse boards and lower tax avoidance, highlighting their role in promoting ethical decision-making. Implications: The findings emphasize the importance of gender diversity in corporate leadership for ethical governance. Future research should further investigate the mechanisms by which gender diversity influences tax ethics, particularly across diverse institutional and cultural contexts. Additionally, longitudinal and qualitative studies are needed to explore how gender-diverse leadership interacts with evolving family business dynamics and regulatory environments over time.